Risk of prevalent HIV infection associated with incarceration among injecting drug users in Bangkok, Thailand: case-control study. Issue 7384 (8th February 2003) - Buavirat, Aumphornpun; Page-Shafer, Kimberly; van Griensven, G J P; Mandel, J S; Evans, J; Chuaratanaphong, J; Chiamwongpat, S; Sacks, R; Moss, A
Abstract: Objectives: To identify risks for HIV infection related to incarceration among injecting drug users in Bangkok, Thailand. Design: Case-control study of sexual and parenteral exposures occurring before, during, and after the most recent incarceration. Setting: Metropolitan Bangkok. Participants: Non-prison based injecting drug users formerly incarcerated for at least six months in the previous five years, with documented HIV serostatus since their most recent release; 175 HIV positive cases and 172 HIV negative controls from methadone clinics. Main outcome measure: Injection of heroin and methamphetamine, sharing of needles, sexual behaviour, and tattooing before, during, and after incarceration. Results: In the month before incarceration cases were more likely than controls to have injected methamphetamine and to have borrowed needles. More cases than controls reported using drugs (60% v 45%; P=0.005) and sharing needles (50% v 31%; P<0.01) in the holding cell before incarceration. Independent risk factors for prevalent HIV infection included injection of methamphetamine before detention (adjusted odds ratio 3.3, 95% confidence interval 1.01 to 10.7), sharing needles in the holding cell (1.9, 1.2 to 3.0), being tattooed while in prison (2.1, 1.3 to 3.4), and borrowing needles after release (2.5, 1.3 to 4.4). Conclusions: Injecting drug users in Bangkok are at significantly increased risk of HIV infection through sharing needles with multiple partners while in holding cells before incarceration. The time spent in holding cells is an important opportunity to provide risk reduction counselling and intervention to reduce the incidence of HIV.